Особенности формирования поликристаллов при спекании под высоким давлением алмазных порошков различной дисперсности - Назарчук, С.Н.; Бочечка, А.А.; Петасюк, Г.А.; Белявина, Н.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Effect of high pressure and temperatures on change of dispersiveness and compaction of diamond powders of various genesis and granularity, on transformation diamond-graphite in the specified powders, and also on hardness of the polycrystals obtained as a result of such action has been studied. Optimum sintering parameters of the investigated powders have been determined.